Comparison of the Influence of Beliefs Regarding Feng Shui in Homes Between the Younger and Older Generations - Virgy Athalia; Listyo Yuwanto (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2025)
Feng Shui is a belief held by individuals of Chinese ethnicity that continues to serve as a basis for home selection, as it is believed to create balance and have a positive impact on homeowners. However, there is still a lack of research examining home selection using Feng Shui from a psychological perspective by comparing younger and older generations. This study used a mixed-methods approach with data collected through a survey. The study used purposive sampling and obtained 59 participants ranging in age from 18 to 75 years, all of whom were of Chinese ethnicity. The results showed that both older and younger generations described Feng Shui as a Chinese spatial arrangement system believed to have positive effects on homeowners’ fortune and health, as well as having logical explanations. Understanding of Feng Shui in both generations was transmitted from parents. However, a unique finding of this study is that participants aged 18–56 obtained information from the internet, whereas printed media were only used by participants aged 41–56. Participants who believed in Feng Shui tended to apply it, while those who did not believe generally did not apply Feng Shui, although some still considered house layout and environmental aspects.